2013
DOI: 10.1080/03004430.2012.752735
|View full text |Cite
|
Sign up to set email alerts
|

Feeding practices of mothers from varied income and racial/ethnic groups

Abstract: OBJECTIVE Relatively few investigators have explored the role of maternal control in describing the feeding behavior of nonwhite parents of preschool-age children. The present study was conducted to examine if controlling feeding behaviors (i.e., restriction and pressuring) varied by income (middle vs. low) and race/ethnicity (white vs. Hispanic), and if they were associated with the BMI of their 4-year-old offspring. METHOD Responses to the “restriction” and “pressure to eat” variables of the Child Feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
2
19
1
1
Order By: Relevance
“…Restrictive feeding practices were significantly associated with enjoyment of food and satiety responsiveness in the African American families, but none of the associations between restriction and child weight status was significant in Hispanic families. In a study of white middle-income and Hispanic low-income mothers and their preschool-age children, Worobey, Borrelli, Espinosa, and Worobey (2013) found lowincome Hispanic mothers self-reported greater use of both restriction and pressure to eat compared with white middle-income mothers, but neither controlling feeding practice predicted children's BMI percentiles. However, as in our study (Table 1) Differences between the two racial/ethnic groups relative to the effect of controlling feeding practices may be the result of differing interpretations of the questionnaire items between the African American and Hispanic families (Anderson, Hughes, Fisher, & Nicklas, 2005).…”
Section: Tablementioning
confidence: 99%
“…Restrictive feeding practices were significantly associated with enjoyment of food and satiety responsiveness in the African American families, but none of the associations between restriction and child weight status was significant in Hispanic families. In a study of white middle-income and Hispanic low-income mothers and their preschool-age children, Worobey, Borrelli, Espinosa, and Worobey (2013) found lowincome Hispanic mothers self-reported greater use of both restriction and pressure to eat compared with white middle-income mothers, but neither controlling feeding practice predicted children's BMI percentiles. However, as in our study (Table 1) Differences between the two racial/ethnic groups relative to the effect of controlling feeding practices may be the result of differing interpretations of the questionnaire items between the African American and Hispanic families (Anderson, Hughes, Fisher, & Nicklas, 2005).…”
Section: Tablementioning
confidence: 99%
“…[19][20][21][22][23][24] On one hand, restriction and pressure to eat has been found to be more common among low-income Hispanic mothers when compared to low-income non-Hispanic whites. 25 On the other hand, Hispanic parents are also more likely to engage in permissive and indulgent feeding during meal times, compared to other racial and ethnic groups. In addition, the child feeding literature has focused primarily on parents and feeding within the home, 31 but 60% of children in the US now spend some time in a child-care setting.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evenness in number of the two groups of mother-child dyads, their different racial/ethnic composition as well as their educational levels presents a confound to income as the explanatory variable; however, this weakness may be a standard criticism of studies that explore the impact of socioeconomic status on maternal behavior (Baughcum et al, 2001;Powers et al, 2006;Worobey et al, 2013). Another weakness lies in the unavailability of BMI data for the Head Start children.…”
Section: Discussionmentioning
confidence: 99%
“…Hughes et al (2006) found low-income Hispanic parents to report more parent-centered/high control feeding strategies as compared to low-income African-American parents, while Worobey, Borelli, Espinosa and Worobey (2013) found low-income Hispanic mothers to be higher in restriction and pressuring to eat relative to middle-income white mothers, with the Hispanic children at higher weight. Some research has shown lower-income African-American mothers to score higher than higher-income white mothers on restriction and pressuring to eat (Spruijt-Metz, Lindquist, Birch, Fisher, & Goran, 2002), but other work shows a more complex association between feeding style and child weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation